Water quality modelling of the Mekong River basin: Climate change and socioeconomics drive flow and nutrient flux changes to the Mekong Delta - Whitehead, P.G.; Jin, L.; Bussi, G.; Voepel, H.E.; Darby, S.E.; Vasilopoulos, G.; Manley, R.; Rodda, H.; Hutton, C.; Hackney, C.; Tri, Van Pham Dang; Hung, N.N. (The Science of the total environment, 2019)
The Mekong delta is recognised as one of the world's most vulnerable mega-deltas, being subject to a range of environmental pressures including sea level rise, increasing population, and changes in flows and nutrients from its upland catchment. With changing climate and socioeconomics there is a need to assess how the Mekong catchment will be affected in terms of the delivery of water and nutrients into the delta system. Here we apply the Integrated Catchment model (INCA) to the whole Mekong River Basin to simulate flow and water quality, including nitrate, ammonia, total phosphorus and soluble reactive phosphorus. The impacts of climate change on all these variables have been assessed across 24 river reaches ranging from the Himalayas down to the delta in Vietnam. We used the UK Met Office PRECIS regionally coupled climate model to downscale precipitation and temperature to the Mekong catchment. This was accomplished using the Global Circulation Model GFDL-CM to provide the boundary conditions under two carbon control strategies, namely representative concentration pathways (RCP) 4.5 and a RCP 8.5 scenario. The RCP 4.5 scenario represents the carbon strategy required to meet the Paris Accord, which aims to limit peak global temperatures to below a 2 °C rise whilst seeking to pursue options that limit temperature rise to 1.5 °C. The RCP 8.5 scenario is associated with a larger 3–4 °C rise. In addition, we also constructed a range of socio-economic scenarios to investigate the potential impacts of changing population, atmospheric pollution, economic growth and land use change up to the 2050s. Results of INCA simulations indicate increases in mean flows of up to 24%, with flood flows in the monsoon period increasing by up to 27%, but with increasing periods of drought up to 2050. A shift in the timing of the monsoon is also simulated, with a 4 week advance in the onset of monsoon flows on average. Decreases in nitrogen and phosphorus concentrations occur primarily due to flow dilution, but fluxes of these nutrients also increase by 5%, which reflects the changing flow, land use change and population changes. Water quality along the Mekong River System (Phosphorus mg/l Left and Nitrate-N mg/l right) [Display omitted] •Climate will alter Mekong flows and seasonal patterns•Flooding will increase in the lower Mekong•Droughts will increase as Dam development increases•Socioeconomic effects will enhance nutrient fluxes into the delta•Eutrophication and increased delta flooding will occur